Antecedents of total factor productivity of Malaysian banks: evidence from semi-parametric Malmquist Productivity Index method - Sufian, Fadzlan; Kamarudin, Fakarudin (Penerbit Universiti Teknologi Malaysia, 2015)
The paper employs the semi-parametric Malmquist Productivity Index (MPI) method to assess the impact of technological change on the obtained total factor productivity of Malaysian banks during the period 1998 –2008. The preferred methodology provides bias-corrected estimates of total factor productivity change along with the information on efforts to catch up to the frontier (efficiency change) from shifts in the frontier (technological change). During the period under study, the empirical findings indicate that the Malaysian banking sector has exhibited productivity progress mainly attributed to technological progress. We also find that shift in the frontier (technological change) positively influence both domestic and foreign banks total factor productivity change.